1999
DOI: 10.1075/eoc.3.2.02gri
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of communication with a spatialized genetic algorithm

Abstract: We extend previous work by modeling evolution of communication using a spatialized genetic algorithm which recombines strategies purely locally.Here cellular automata are used as a spatialized environment in which individuals gain points by feeding from drifting food sources and are 'harmed' if they fail to hide from migrating predators. Our individuals are capable of making one of two arbitrary sounds, heard only locally by their immediate neighbors. They can respond to sounds from their neighbors by opening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 11 publications
2
29
0
Order By: Relevance
“…The AM²s inhabiting a given niche interact with the environment in two ways: they feed and they can hide themselves to avoid the attacks of three kinds of predators -α , β and γ -which put them in three internal states (the reader will find more details about this scenario in (Grim et al, 2001)). Suppose the AM²s involved in this scenario engage in a kind of adaptive language game, such as the guess game (Steels, 2005).…”
Section: From Grounded Symbols To Grounded Communication and Abstractmentioning
confidence: 99%
“…The AM²s inhabiting a given niche interact with the environment in two ways: they feed and they can hide themselves to avoid the attacks of three kinds of predators -α , β and γ -which put them in three internal states (the reader will find more details about this scenario in (Grim et al, 2001)). Suppose the AM²s involved in this scenario engage in a kind of adaptive language game, such as the guess game (Steels, 2005).…”
Section: From Grounded Symbols To Grounded Communication and Abstractmentioning
confidence: 99%
“…Within neural net models in particular, symmetrical rewards for 'successful communication' characterize Werner and Dyer (1991), Saunders and Pollack (1996), and Hutchins and Hazelhurst (1995). 4 In earlier studies we have considered similar environments in which strategy change was by pure imitation of successful neighbours (Grim et al, 2000) or by genetic algorithm crossover with successful neighbours (Grim et al, 2001). In these studies we found similar results, indicating that the forces driving emergence of information transfer are inherent in the environmental structure rather than in the specific mode of strategy change.…”
Section: Notesmentioning
confidence: 52%
“…In this sense, language is like a cloud of birds which attains and keeps its coherence based on individual rules enacted by each bird. (p. 2) Another essential aspect of the model offered here is spatialization, carried over from our own previous work in both cooperation and simpler models for communication (Grim, 1995(Grim, , 1996Grim et al, 1998Grim et al, , 2000Grim et al, , 2001. Our community is modeled as a two-dimensional cellular automata array.…”
Section: A Use-based Model Of Meaning and Informationmentioning
confidence: 99%
“…In later studies, we explored (1) behaviours that signal an alarm when a predator is present, whether or not the individual is harmed, and (2) models in which twice as many predators as food sources are used. The latter is the environment emphasized here-see also Grim et al (2001). 8.…”
Section: Resultsmentioning
confidence: 97%